2019
DOI: 10.1080/08998280.2019.1641046
|View full text |Cite
|
Sign up to set email alerts
|

Resident identification of feedback and teaching on rounds

Abstract: Feedback and teaching occur regularly on teaching hospital wards. Although feedback has important implications for resident learning, residents often report that they receive little feedback. The significant overlap of teaching and feedback in clinical education may contribute to resident difficulty with feedback identification. We sent a survey with seven scenarios to internal medicine residents across the country. Two of the scenarios contained teaching, two contained feedback, and three contained combined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Previous work showed that residents have difficulty identifying and differentiating feedback and teaching in the clinical setting [ 7 ]. This analysis demonstrates one possible reason for this difficulty is that feedback and teaching are ubiquitous in the clinical learning environment, creating confusion in their distinction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work showed that residents have difficulty identifying and differentiating feedback and teaching in the clinical setting [ 7 ]. This analysis demonstrates one possible reason for this difficulty is that feedback and teaching are ubiquitous in the clinical learning environment, creating confusion in their distinction.…”
Section: Discussionmentioning
confidence: 99%
“…To explore why residents might have difficulty recognizing feedback when it occurs with teaching, these questions were followed by an exercise asking participants to compare 2 scenarios. The scenarios were identified by residents and faculty in our prior study as one of stand-alone teaching and a second of both feedback and teaching [ 7 ]. Focus groups were not repeated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, residents frequently confuse teaching and feedback or fail to recognize when educators are providing feedback. 28 The SPIKES framework incorporates an invitation to provide feedback which could indicate to learners that feedback is occurring when they otherwise would not recognize it.…”
Section: Discussionmentioning
confidence: 99%